Makna, Tolok Ukur, Pemahaman, dan Sikap Pengadilan di Indonesia terhadap Iktikad Baik dalam Pelaksanaan Kontrak - Ridwan Khairandy (Fakultas Hukum Universitas Islam Indonesia, 2009)
This research focuses three legal issues deal to the meaning, legal tests, and understanding and attitude Indonesian court about good faith on contract performance. Using the descriptive analysis with normative juridical approach and comaprative, and library data, this research reveals: First of all, the meaning of good faith on contract performance is not universal, but there is a tendency its meaning refers to objective good faith. Second, legal test of that good faith uses objective tests, namely reasonableness and equity. Lastly, Court in Indonesia does not have deep understanding of good faith on contract performanceKey word : good faith, reasonableness, and equity